Learning disabilities: Different theoretical approaches and ways of treatment - Rimkutė, E.; Dovydaitienė, M. (Psichologija, 2011)
The article examines some methodological problems of research and treatment of learning disabilities. Analytic and holistic approaches to learning disabilities are introduced. Mainstream academic psychology is currently dominated by the analytic approach, which seeks to reduce complex phenomena to its parts in order to study and understand existing interactions between them. A review of literature reveals, that generally learning disabilities are defined in terms of deficits of various cognitive and language abilities and skills necessary for learning. Most often offered treatment procedures are based on programs that focus on improving deficient skills through repetition of various cognitive exercises. We put special emphasis on holistic approach which is presented through theorizing and the treatment of learning disabilities by French audio-psycho-phonologist Alfred Tomatis. According to A. Tomatis, neither normal nor abnormal behaviour can be understood without relating it to 1) the functioning of the whole organism, and 2) the historical and individual developmental processes. From his point of view, language, as a tool for communication, plays a very important role in the humanization of an individual. Individual personal development also confirms that the need for communication emerges already in the prenatal stage, when the link between foetus and mother is maintained, as the foetus hears from the 5th month of intrauterine life. The desire to communicate is implicit in the realization of human consciousness. Considering learning difficulties which are related with written language A. Tomatis claims that it is communication — primarily listening — disorder. The treatment, proposed by A. Tomatis, consists in teaching a person to use his ear as an apparatus capable of listening. He developed an electronic device called Electronic Ear designed to modify the way in which a subject listened and to help him improve language, learning and communication skills. Practitioners using A. Tomatis method confirm its effectiveness. However, it would be very difficult to evaluate his method through analitical experiments that would satisfy academic psychology, which remains skeptical. To contribute to the progress in understanding and treatment of learning disabilities academic psychology should pay more attention to the ideas approved in practice and to find more flexible ways of detection and evaluation of personal change.